Evaluation of the Efficiency of Wastewater Treatment Plants in the Removal of Common Antibiotics from Municipal Wastewater in Hamadan, Iran - Reza Shokoohi; Abdollah Dargahi; Razieh Khamutian; Yaser Vaziri (Hamadan University of Medical Sciences, 2017)
The presence of antibiotics in the environment, especially aquatic environments, is a major health and environmental concern.Wastewater treatment plants play an important role in the treatment of municipal and industrial wastewater and removal of contaminants.The aim of this study was to determine the concentration of prevalent antibiotics in municipal wastewater of Hamadan,Iran and to evaluate the removal efficiency of wastewater treatment plants. During 3 months (April, May, and June 2016), a total of 12 composite influent and effluent samples were collected from the wastewater treatment plants. Solid-phase extraction (SPE) was used for preparing the samples, which were then analyzed using high-performance liquid chromatography (HPLC) with UV detection.Based on the analysis of 6 antibiotics, three antibiotics, including amoxicillin, imipenem, and cefixime, were detected, and their concentrations were measured at 1.6, 10.7, and 5.8 ug/L, respectively. The removal efficiency of these antibiotics in wastewater treatment plants was 55.66%, 34.01%, and 24.33%, respectively. Due to the presence of examined antibiotics in the effluent and influent wastewater treatment plants, they might cause direct and indirect effects on human health and environment if proper measures are not taken by the authorities. Since the removal of these antibiotics from wastewater treatment plants is relatively poor, it is suggested to use advanced wastewater treatment plants to reduce antibiotics in effluent wastewater and decrease the adverse effects of these micropollutants.